Hypatia’s Politico-Philosophical Parrhesia: A Foucauldian Analysis of Kingsley’s Hypatia - Maleki, Nasser; Haj’jari, Mohammad Javad (Historein, 2018)
Using the model of the early Christian Church in his novel Hypatia, Charles Kingsley criticised mid-nineteenth-century Roman Catholicism for its bigotry. As such, his historiographic rendering of Hypatia’s life highlights the power relations between the early Christian Church and Hellenistic philosophy as a politico-religious allegory against mid-nineteenth-century Catholicism and its intolerance of female intellectuality and personal faith. Highlighting Kingsley’s views accordingly, a Foucauldian analysis of Hypatia’s politico-philosophical parrhesia, that is, speaking the truth in the light of political philosophy before Cyril’s early Christian theocracy, seems intriguing. Hypatia represents an illuminating world of power struggles between Hypatia’s peaceful intellectuality and the early Christian bigotry, a fact represented in Hypatia’s virtue and knowledge before the blind fundamentalism of the religious oligarchy and the outrageous extremism of the early Christian mob, only to culminate in the lynching of the innocent Hypatia. Kingsley’s historiographic novel thus tries to historicise his attacks against nineteenth-century Tractarian Catholic extremes regarding the practice of religion and gender issues.